Distal Renal Tubular Acidosis as complication of Mixed Connective Tissue Disorder with autoimmune hypothyroidism- a case report (Bangladesh Journal of Medicine, 2016)
Renal tubular acidosis (RTA) is a constellation of syndromes arising from different derangements of tubular acid transport. Multiple associations have been established with renal tubular acidosis. We report a case of distal renal tubular acidosis which may be associated with undifferentiated connective tissue disease in which patient is also having autoimmune hypothyroidism along with that is not very common.Bangladesh J Medicine Jan 2016; 27(1) : 37-39